Novel prediction tools for sep events. (Research'eu results magazine)
Advancing our capacity to predict 'Solar energetic particle' (SEP) events is essential to the smooth running of human spaceflights beyond Earth. New space weather prediction tools developed under the HESPERIA project have reached a milestone, notably by enabling earlier prediction of 'Ground level enhancement' (GLE) events- which pose severe radiation hazards to astronauts and tend to disrupt airline communication.